IDENTIFIKASI PUTUSAN KARIR MAHASISWA UNIVERSITAS TEKNOLOGI YOGYAKARTA MENGGUNAKAN APLIKASI ANDROID MIHG (MULTIPLE INTELLIGENCE BY HOWARD GARDNER) - Widi Fajar Widyatmoko; Ari Prasetyoaji (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2021)
The future challenges of higher education students for determining their future career in the era of industrial revolution 4.0 and society 5.0, getting more complex. Student may facing career uncertainty, lack of access to information and career development programs, and economic and technological challenges. Previous research shown many student need for career guidance to be addressed for choosing their course study. Student at the University level are grouped into groups of fields according to their choice of interests. Research findings in the field reveal that not a few students have a career decision level that is still not optimal, whereas many as 71% of students still need help regarding career decisions. The existence of this individual intelligence identification application can help students in making career decisions. This is shown by the results of the media use test in the field that 89% of UTY students experienced an increase in career decisions after using Howard Gardner's Multiple intelligence identification application. Thus, the application of multiple intelligence in helping to make career decisions is said to be suitable as a medium to help students make career decisions for UTY students.